Sistema de liberação de substâncias a partir de filmes nanotexturizados de TiO2 - Lopes, Paula Prenholatto (2021)
Researches involving drug delivery systems based on TiO2 nanotubes suggest a great potential as a platform to be used in the biomedical area, mainly due to its biocompatibility. The drugs loaded in the nanostructures also constitute an essential part of the post-operative treatment to combat the rejection of the prosthesis by bacterial adhesion. Focusing on natural therapeutic agents to mitigate microbial infections seems to be a promising alternative source. Furthermore, the phytochemicals present in medicinal plants play an essential role in determining antimicrobial activity. The present study aims to modify the surface of the commercial Ti (99.5%) by forming TiO2 nanotubes by anodic oxidation. The used electrolyte solution containing fluoride ions and solution of Simulated Body Fluid. The samples were characterized with Scanning Electron Microscopy and Contact Angle. After nanotubes formation, aqueous solutions of methylene blue and alcoholic solutions of green propolis extract (Apis Flora® 70%) and eugenol (Biodinâmica®) were used as antimicrobial agents and they were deposited on top of the samples with and without nanotubes, for further comparison. Also, the effect of samples coated with a layer of Alginate was verified. The process of releasing the substances was carried out in PBS buffer solution at 37ºC. The aliquots removed at predetermined times were analyzed on the UV-vis spectrophotometer to obtain the release curve of each substance. The released samples showed an initial burst followed by a stabilization phase, indicating the release of loaded loaded substances. The Alginate coating acted as a diffusional barrier, optimizing release control to delay the initial burst and increase the total delivery time of methylene blue, green propolis, and eugenol.